Importance of Integrated Vector Management (IVM) for the Control of Vector Borne Diseases - Mosleh Uddin, Abu Noman Mohammed; Jewel, Mehedi Hasan (Journal of Armed Forces Medical College, Bangladesh, 2024)
Abstract not available JAFMC Bangladesh, Vol 20, No 1(June 2024):1-2